Prevalence and antimicrobial susceptibility of methicillin resistant Staphylococcus aureus in tertiary care hospital - Chandrakar, Sunita; Enam, Sk. Khairul; Panda, Animesh; Bawankar, Smita; Chandi, Dhruba Hari (Asian Journal of Medical Sciences, 2016)
Background : Methicillin Resistant Staphylococcus aureus (MRSA) infections are important causes of morbidity, mortality in hospitals & the community worldwide. MRSA has been known to acquire resistance to most antibiotics like ?- lactams & aminoglycosides so these strains are more virulent. Aims and Objectives : Therefore the knowledge & determination of prevalence of MRSA & their current antimicrobial profile becomes necessary to the clinicians to avoid clinical complications from community-acquired & hospital acquired MRSA infection. Materials and Methods : A total of 205 of different samples from different clinical specialties were collected & processed by appropriate microbiological technique like staining, culture, biochemical test & antimicrobial susceptibility test by the use of different antibiotic discs. Results : The present study shows that 47 out of 105 men comprising 44.76%, whereas in case of females it was 29% i.e 29 out of 100 cases. MRSA percentage of males was higher than the MRSA percentage of female. It proves that men were more prone to acquire the infection by MRSA strain. Out of 205 clinical samples, 76 were identified as MRSA so the prevalence rate was 37.07% but all the multidrug resistance MRSA were mostly sensitive towards antibiotics like Vancomycin (100%), Rifampicin (100%), Amoxicillin (77.77%) & Amikacin (61.19). Conclusion : In conclusion, vancomycin are considered for treatment to eradicate the MRSA. Asian Journal of Medical Sciences Vol. 7(3) 2016 72-77